Strategi Guru Kelas dalam Mengatasi Kesulitan Belajar Siswa pada Pembelajaran Tematik - Masrurinnisa, Aulia; Rosyidah, Binti; Inayati, Denik Rohmah (IERA, Islamic Education and Research Academy, 2020)
This study delves into the pivotal role of the learning process for students in determining educational success. Within the school environment, students encounter specific learning challenges, including difficulties in grasping instructional content provided by teachers. These challenges manifest in diverse behavioral ways, directly or indirectly affecting the overall learning environment. Consequently, effective strategies employed by teachers to address these challenges are paramount. Focusing on fourth-grade students at MI Islamiyah Jatipunggur Lengkong Nganjuk, this study investigates the factors contributing to student learning challenges in thematic lesson theme 8, explores teacher strategies to mitigate these difficulties, and identifies implementation obstacles. Employing qualitative methodology, data collection involves observation, interviews, and documentation. The data undergoes descriptive analysis, including reduction, presentation, and verification through triangulation. The findings unveil two primary factors contributing to learning challenges: internal and external. Teachers adeptly employ strategies encompassing expository, cooperative, and contextual approaches, along with providing additional instruction time for struggling students. Nonetheless, resource constraints, time allocation issues, and effective student grouping pose implementation challenges for these strategies.